Clinical anatomy and surgical significance of the lingual foramina and their canals. Issue 2 (9th February 2017) - He, Puhan; Truong, Mindy K.; Adeeb, Nimer; Tubbs, R. Shane; Iwanaga, Joe
Abstract : The lingual foramina and canals can be categorized as median or lateral based on their relation to the midline of the mandible. Investigation of the mandibular lingual region is often done with gross anatomical dissections of cadavers, 2D panoramic radiographic imaging, CT, and cone beam CT (CBCT). While gross studies are the most reliable at qualifying canal contents and course, CBCT proved to be superior to other radiographic techniques for visualizing lingual foramina and canals. The submental and sublingual arteries, and their branches are found in the lingual vascular canals. There is tremendous variation between individuals in terms of the course of the lingual canals and their anastomosis with other vascular canals. Performing the dental implantation procedures in the anterior and posterior regions of the mandible can result in perforation of the lingual cortex, which could injure the arteries that lie within the lingual canal. If hemorrhage occurs, it could lead to life‐threatening upper airway obstruction. Pre‐surgical investigation to identify the diameter of the lingual foramina and canal as well as their distance from the alveolar process might be necessary to prevent hemorrhage for all patients. Clin. Anat. 30:194–204, 2017. © 2017 Wiley Periodicals, Inc.